Molecular and immunological profiling of typhoid carriers and salmonella typhi: towards development of preventive and investigative diagnostics - Ismail, Asma (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2011)
Detection of typhoid carriers is not easy due to the lack of effective lab tests for carriers. If we can design diagnostic tests to detect for carriers, we can provide treatment, create a carrier registry and study the carriers himself/herself - (Fundamental and clinical studies), isolate S.Typhi from the carriers, sequence its DNA and compare that to those isolated from acute cases - (Molecular studies). In fact many studies (goldmine) can be done if we can detect for carriers. In this proposal we undertake to study individuals who were previously culture positive for Salmonella Typhi for a minimum of 1 year with respect to the following objectives: • To develop new methods to identify possible carriers • To determine the OMP antigens that are antigenically specific to typhoid carriers • To determine the immunological factors that predispose individuals to become carriers • To sequence and compare the DNA profiles of S. Typhi isolated from acute cases, carrier cases, the environment and the S. Typhi DNA sequence (gene bank) • To develop diagnostics for detection of typhoid carriers • Perform evaluation of the developed tests Among the achievements of studies include: Establishing the first carrier registry in Kelantan/Malaysia Our PCR assay could match the culture results suggesting our PCR test could be an alternative method to detect for carriers When screened for biomarkers, the carrier lgG and lgA showed that it recognized only the 50kDa antigen of S.Typhi. The TYPHIDOT-C was shown to be a potential serological screening tool to detect for possible carriers. Established the first genome sequence bank of S.Typhi that are isolated from confirmed carriers from Malaysia (MyTyphoidgenom). The specific sites could not be considered of value as epidemiological markers as well as diagnostic purposes since they are no unique sequences for S. Typhi isolated from typhoid carriers. This revealed that typhoid carriage is NOT due to the organism but rather due to host factors. Immunological profiling of the host showed that reduced levels of TH1 and TH2 cytokines might suggest a carrier status The candidate gene (2136 bp Polynucleotide phosphorylase gene) was used to test if typhoid carrier state in humans was due to a mutation in this gene that was reported to determine virulence and carrier status of S. Typhimurium in mice. Results showed that there were 11 silent mutations in the PNPase gene (hence did not affect protein expression). Hence the findings reported for S, Typhimurium in mice cannot be extrapolated to S.Typhi that affect only humans In developing the dipstick method for Antibody carrier detection, we have shown by POC that the dipstick method is working in our laboratory for detection of lgA. When outsourced for the cassette format for both lgG and lgA requires more time for fine tuning.